Using discrete simulation to support internal logistics process design - Campos, Tiago M.C. (2017)
The objective of this paper is to present the developments of an ongoing project that aims at implementing an internal materials movement system using autonomous vehicles for supporting logistics processes. In particular the project focus on the movement of final products, from assembly lines to the expedition warehouse and the supply of packaging materials (customer packages), from the raw materials warehouse to the assembly lines. This process is currently carried out by two stackers, in a milk-run environment and, in the context of this project, an innovative solution is proposed to improve the performance of the supply and pickup processes, transforming and optimizing an entirely manual process into an automated one. The main challenge was to investigate the impact on the existing internal logistic system of the new solution and, simultaneously, to explore if new management strategies are needed to satisfy both throughput levels and overall supply chain needs. A simulation model was developed using ARENA Simulation Software to get insights concerning the new challenges posed by the solution to be adopted. Results have revealed that the use of simulation allowed the assessment of the impact of the new internal logistics solution and played a critical role to identify the best dispatching rules to schedule transportation orders in such a complex system. This research shows the flexibility of the simulation tool to address several complex management issues simultaneously that arises in the context of innovative solutions aligned with industry 4.0 challenges.